The Efektivitas Model Pembelajaran Flipped-Guided Inquiry Based Learning Pada Materi Kesetimbangan Kimia terhadap Hasil Belajar Siswa Kelas XI Di SMA Negeri 8 Padang - Dini Candani; Mawardi Mawardi (Universitas Negeri Padang, 2023)
This research aims to determine the level of effectiveness of the use of the Flipped-Guided Inquiry Based Learning Learning Model on Chemical Equilibrium Materials. The research method used was a quasi-experimental with non-equivalent control group design. The population in this study were students of class XI MIPA SMA N 8 Padang. The sample class was selected based on the purposive sampling technique, so that the XI MIPA 2 class was obtained as the experimental class and the XI MIPA 1 class as the control class. Data were analyzed using N-gain test and t-test. The instrument of this research is a test of learning outcomes by giving a pretest and posttest in the form of objective questions that are arranged based on the learning objectives. The results showed that the average pretest and posttest scores had different results, namely 53.125 in the experimental class and 48.939 in the control class. So that the average N-gain test is 0.78 in the high category experimental class and 0.68 moderate category control class. It is also supported by the results of the hypothesis test, namely the t-test, with Tcount (3.327) > Ttable (1.669) at a significant level of 0.05 with dk = 63 and probability t0.95. It can be concluded that the Flipped-Guided Inquiry Based Learning Model on Chemical Equilibrium Material is proven to be effective in improving student learning outcomes.